The Effect of Financial Literacy, Impulsive Buying, Self-Control and Cashless Payment on Financial Management: (Study on FEB Students at Bandar Lampung University) - Gunawan, Sthefanny; Khairudin, Khairudin (LPPPIPublishing, 2026)
The purpose of this study was to examine how financial literacy, impulsive buying, self-control, and cashless payments influence the financial management of students at the Faculty of Economics and Business, Bandar Lampung University. The methodology used was quantitative, with a causal associative method. The study population consisted of all 856 FEB students at Bandar Lampung University, with a sample of 90 respondents selected using the Slovin formula and a purposive sampling approach. Data were collected through a survey and processed with the Statistical Package for the Social Sciences (SPSS). The analysis stages included descriptive analysis, data quality testing (validity and reliability tests), classical assumption testing (normality, multicollinearity, and heteroscedasticity tests), and multiple linear regression analysis. Hypothesis testing was conducted using the t-test, F-test, and coefficient of determination (R²). The findings of this study are expected to provide insight into the variables that influence student financial management, as well as serve as a basis for students and academic institutions to consider when promoting higher literacy and better financial behavior.